2014
DOI: 10.3233/ves-140510
|View full text |Cite
|
Sign up to set email alerts
|

Cervical vestibular evoked myogenic potentials and caloric test results in individuals with auditory neuropathy spectrum disorders

Abstract: Auditory neuropathy spectrum disorder is a type of hearing loss where outer hair cell function are normal (as evidenced by the preservation of OAEs and cochlear microphonics), whereas auditory nerve functions are abnormal (as evidenced by abnormal auditory brainstem evoked potentials beginning with wave I of the ABR) and acoustic reflexes to ipsilateral and contralateral tones are absent [32]. It is likely that in cases with auditory neuropathy spectrum disorder not only the cochlear nerve, but also the vestib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Previous studies have reported substantial vestibular nerve damage in individuals with ANSD. 12 13 15 The abnormal results on the cervical VEMP suggests a sacculo-collic pathway dysfunction affecting the inferior vestibular nerve. 12 In addition, the ocular VEMP is also affected, which is suggestive of abnormal superior vestibular nerve functioning.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have reported substantial vestibular nerve damage in individuals with ANSD. 12 13 15 The abnormal results on the cervical VEMP suggests a sacculo-collic pathway dysfunction affecting the inferior vestibular nerve. 12 In addition, the ocular VEMP is also affected, which is suggestive of abnormal superior vestibular nerve functioning.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies have reported vestibular nerve involvement in individuals with ANSD. 12 13 14 15 Despite this, audiological rehabilitation has always been the primary focus in individuals with this disease. Thus, the present study recommends the assessment of the real life handicap experienced because of vestibular problems in individuals with ANSD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Adamec et al 9 ), benign paroxysmal positional vertigo (Singh & Apeksha 10 ), auditory neuropathy spectrum disorder (Sujeet et al 11 ) and superior semicircular canal dehiscence syndrome (Janky et al 12 ). Similar to cVEMPs, VEMPs are also elicited at the level of the masseter muscle, also known as masseter VEMPs (mVEMPs).…”
Section: Accepted Manuscriptmentioning
confidence: 99%